Moonlight functions of glycolytic enzymes in cancer - Shegay, Petr V.; Shatova, Olga P.; Zabolotneva, Anastasia A.; Shestopalov, Aleksandr V.; Kaprin, Andrei D. (Frontiers in Molecular Biosciences, 2023)
Since an extensive genome research has started, basic principle “one gene – one protein – one function” was significantly revised. Many proteins with more than one function were identified and characterized as “moonlighting” proteins, which activity depend not only on structural peculiarities but also on compartmentation and metabolic environment. It turned out that “housekeeping” glycolytic enzymes show important moonlight functions such as control of development, proliferation, apoptosis, migration, regulation of transcription and cell signaling. Glycolytic enzymes emerged very early in evolution and because of the limited content of genomes, they could be used as ancient regulators for intercellular and intracellular communication. The multifunctionality of the constitutively expressed enzymes began to serve cancer cell survival and growth. In the present review we discuss some moonlight functions of glycolytic enzymes that important for malignant transformation and tumor growth.